The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1523/jneurosci.0395-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Memory Impairment in Transgenic Alzheimer Mice Requires Cellular Prion Protein

Abstract: Soluble oligomers of the amyloid-β (Aβ) peptide are thought to play a key role in the pathophysiology of Alzheimer’s disease (AD). Recently, we reported that synthetic Aβ oligomers bind to cellular prion protein (PrPC) and that this interaction is required for suppression of synaptic plasticity in hippocampal slices by oligomeric Aβ peptide. We hypothesized that PrPC is essential for the ability of brain-derived Aβ to suppress cognitive function. Here, we crossed familial AD transgenes encoding APPswe and PSen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
402
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(426 citation statements)
references
References 62 publications
20
402
2
2
Order By: Relevance
“…It is possible that, as PrP Sc begins to propagate, early loss of function of PrP C at the neuronal surface may interfere with monoaminergic signaling by modulating G-protein-coupled receptor responses. In addition, the evidence that implicates PrP C as a binding partner of A␤ peptide oligomers (37) extends the potential relevance of our data to neuropsychiatric manifestations of Alzheimer disease (105). Indeed, the behavioral deficits that indicate a depressive-like behavior of PrP C -null animals are reminiscent of those described in mice subject to injections of A␤ peptide oligomers (106).…”
Section: Discussionsupporting
confidence: 68%
“…It is possible that, as PrP Sc begins to propagate, early loss of function of PrP C at the neuronal surface may interfere with monoaminergic signaling by modulating G-protein-coupled receptor responses. In addition, the evidence that implicates PrP C as a binding partner of A␤ peptide oligomers (37) extends the potential relevance of our data to neuropsychiatric manifestations of Alzheimer disease (105). Indeed, the behavioral deficits that indicate a depressive-like behavior of PrP C -null animals are reminiscent of those described in mice subject to injections of A␤ peptide oligomers (106).…”
Section: Discussionsupporting
confidence: 68%
“…Here there is a spread of data. While improvements in this parameter were noted in TgPS1delta E9/APPSwe mice deleted for the PrP gene, 52 there was no such effect of Prnp genotype in the J20 line of TgAD mice. 53 TgCRND8 mice 58 are a yet different line of TgAPP mice with more profound deposition of Aβ, starting at 3 months of age, and in our own trial studies 90% of neonatal mice lacking one copy of Prnp did not survive to 100 days of age (Fig.…”
Section: Proteolytic Pathwaysmentioning
confidence: 78%
“…Furthermore, using monoclonal antibodies directed at two different PrP C epitopes, these and other authors successfully blocked the Aβ-mediated disruption of synaptic plasticity. 51 With regards to memory function in intact animals, Gimbel and coworkers reported that PrP gene deletion improved impairment in the Morris water maze in a transgenic model of AD, 52 a different transgenic AD line did not yield the same effects, 53 and another lab could not score an effect of Prnp genotype on a behavioral task when Aβ oligomers were applied as toxic reagents. 54 …”
Section: Proteolytic Pathwaysmentioning
confidence: 99%
“…injury and cell death have been proposed. 4,19 Electrophysiologic studies also impute that PrP C mediates effects of Aβ assemblies. 20 In animal experiments it was possible to counteract detrimental effects of Aβ and rescue parts of cognitive function by applying antibodies directed against PrP C .…”
Section: Methodsmentioning
confidence: 99%
“…20 In animal experiments it was possible to counteract detrimental effects of Aβ and rescue parts of cognitive function by applying antibodies directed against PrP C . 19,[21][22][23] Considering all these findings, it stands to reason that further research on this topic is necessary, since PrP C might be useful as an AD biomarker as well as a potential therapeutic target. 24 Put into a clinical perspective, Meyne et al were able to demonstrate levels of CSF PrP C to be decreased in various neurodegenerative diseases including AD.…”
Section: Methodsmentioning
confidence: 99%